Las estrategias de afrontamiento ante el divorcio y/o separación parental en los estudiantes de los novenos años de educaciòn bàsica del colegio de bachillerato La Dolorosa, periodo 2014 – 2015 - Sozoranga Cabrera, Rosa Carmen (2015)
Titling this paper aims to analyze strategies for coping with divorce and / or parental separation in the ninth year students; materials; scientific, analytical, synthetic, inductive, deductive; a survey and coping scale for adolescents (ASC 96) was applied. Results, 15.66 % often used coping strategy unproductive (ignore the problem) before the divorce and / or parental separation. The 35.24 % of the parents are divorced, separated the 24.76 % and 20.95% married; likewise the 13.63 % of students with married parents use coping aimed at resolving the problem sometimes; conclusions; In a large percentage of their students are divorced and / or separated parents why try to avoid the problem by using a strategy unproductive ignoring the problem